Pengaruh Model Pembelajaran Kooperatif Tipe Think-Pair-Share Dengan Metode Eksperimen Terhadap Hasil Belajar Peserta Didik MAN Lombok Barat Tahun Pelajaran 2017/2018 - Juliana Audina Pratiningsih; Hairunnisyah Sahidu; Kosim Kosim (Department of Physics Education, Universitas Mataram, 2018)
Abstract - This research is aimed to find the effect of cooperative model learning think pair share type with experiment method toward learning physics result of the students at man west Lombok in academic year 2017/2018. The kind of this research is quasi experiment with Untreated control group design with pretest-posttest research design. The population of this research is all of the XI students of MAN West Lombok which consist of 34 students. Sampling jenuh technique is a way of taking the sample, while XI IPA 1 students as experiment class and XI IPA 2 as control class. The instruments that used are; multiple choice test and observation sheet. The amount of the multiple choice test are 25 questions where the test before has been through validity test, reliability, different capacity and standard of questions difficulty, while the observation sheet used to measure the affective and psychomotor score. Based on the result of the research that achieved from the mean score for pretest of experiment class is 40,19 and control class is 37,45, while the mean score of post-test experiment class is 73,52 and control class is 51,27. The hypothesis of the research is tested using t-test polled varians with significant standard 5% and achieved tresult 7,646 and ttable ÃÂ 2,021. Based on the criteria of hypothesis test, if tresult > ttable, it means Ho released and Ha accepted, where it can conclude that there is a effect of cooperative model learning think pair share type with experiment method toward learning physics result of the students at man west Lombok in academic year 2017/2018.